BioMeta: modular reprogrammable metasurface for noninvasive human respiration monitoring - Li Xin Yu; Chen Long; Qin Shi Long; Zhao Ke Zhan; Cai Zi Xuan; Peng Qiao Cong; Ma Qian; You Jian Wei; Cui Tie Jun (Nanophotonics)
Human vital-sign sensing using electromagnetic wave has emerged as a promising technology for the noninvasive monitoring of individuals’ health status. Here, a modular reprogrammable metasurface system is presented to suppress noise in noninvasive human respiration sensing. The proposed reprogrammable Biological Metasurface (BioMeta) provides three-dimensional dynamic control over wavefront shaping and thus can reduce interference from human limb motions. This capability allows the system to acquire health data accurately and reliably and is particularly beneficial in real-world environments where human subjects may change posture or location frequently. Furthermore, the meta-atom in BioMeta is modular and detachable, thereby resulting in reusable properties and promoting environmental sustainability. Meanwhile, the characteristics of mechanical control enable BioMeta to operate without continuous power supply, thus saving energy to a certain extent. A contactless human respiration sensing prototype based on the proposed BioMeta is demonstrated. Experimental results validate that the BioMeta system can accurately monitor the breathing of multiple individuals with limb movements by means of time multiplexing, with an average estimation error of 0.5 respiration per minute. The proposed system enhances sensing accuracy and reliability for noninvasive human respiration monitoring, presenting a versatile and environmentally friendly solution for applications like elderly care and disease monitoring.